2005
DOI: 10.1103/physreve.72.041601
|View full text |Cite
|
Sign up to set email alerts
|

Critical adsorption at silicon surfaces in binary liquid mixtures

Abstract: In critical binary liquid mixtures the preferential adsorption that occurs at liquid-vapor or liquid-solid surfaces is expected to be described by a universal surface scaling function. In this paper, we show that aniline strongly adsorbs at an oxide-coated Si wafer surface from a critical mixture of aniline + cyclohexane where this solid-liquid adsorption can be described by the same universal function found at liquid-vapor surfaces. For a tetrabromoethane + n-dodecane critical mixture the n-dodecane adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[8] provides a review of experimental results, more recent studies are found in Refs. [9][10][11][12][13][14][15]. While most theoretical investigations concern with adsorption on a plane [16][17][18][19][20][21][22], the case of a nonplanar geometry was studied in Refs.…”
Section: Order-parameter Profiles and Local Susceptibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] provides a review of experimental results, more recent studies are found in Refs. [9][10][11][12][13][14][15]. While most theoretical investigations concern with adsorption on a plane [16][17][18][19][20][21][22], the case of a nonplanar geometry was studied in Refs.…”
Section: Order-parameter Profiles and Local Susceptibilitiesmentioning
confidence: 99%
“…[8] for a review, and Refs. [9][10][11][12][13][14][15] for more recent results), as well as theoretical investigations (see, e.g., Refs. [16][17][18][19][20][21][22][23][24][25][26]).…”
Section: Introductionmentioning
confidence: 99%
“…For adsorption experiments, especially on planar interfaces, it is essential that the surface be well cleaned and that the oxidation of the surface be reproducible, but to achieve this, researchers employ a wide variety of cleaning and treatment methods. For example, silica can be exposed to a gas flame or treated with a piranha solution (70% H 2 SO 4 and 30% H 2 O 2 ), , with UV ozone, or with different types of plasma such as air, nitrogen, argon, or oxygen . DeRosa et al compared a number of these methods (UV ozone and oxygen and H 2 O plasma).…”
Section: Introductionmentioning
confidence: 99%